2015
DOI: 10.1002/ece3.1652
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of soil microbial communities inhabiting vineyards and native sclerophyllous forests in central Chile

Abstract: Natural ecosystems provide services to agriculture such as pest control, soil nutrients, and key microbial components. These services and others in turn provide essential elements that fuel biomass productivity. Responsible agricultural management and conservation of natural habitats can enhance these ecosystem services. Vineyards are currently driving land‐use changes in many Mediterranean ecosystems. These land‐use changes could have important effects on the supporting ecosystems services related to the soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 69 publications
2
12
0
1
Order By: Relevance
“…Comparing bacterial phyla and genera, we did not find differences in relative abundances between forest and vineyard soils. Additionally, we found that diversity indices and microbial community structure were similar between forest and vineyard soils; this agrees with our previous work performed using T-RFLPs (Castañeda et al, 2015). Conversely, these findings differ from previous evidence suggesting that bacterial communities differ between forest and managed soils (García-Orenes et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Comparing bacterial phyla and genera, we did not find differences in relative abundances between forest and vineyard soils. Additionally, we found that diversity indices and microbial community structure were similar between forest and vineyard soils; this agrees with our previous work performed using T-RFLPs (Castañeda et al, 2015). Conversely, these findings differ from previous evidence suggesting that bacterial communities differ between forest and managed soils (García-Orenes et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…From a comparative point-of-view, we found similar fungal abundance between forest and vineyard soils. Interestingly, our previous work employing T-RFLPs showed that fungal community structure differed between forest and vineyard soils (Castañeda et al, 2015); this agrees with another T-RFLP-based study that shows that fungal diversity differs between native Eucalyptus forests and Pinus plantations in Australia (Kasel, Bennett & Tibbits, 2008). It should be noted that the lack of differences in fungal abundances in the present study might be related to the low representation of fungal sequences in the soil samples.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Castañeda et al, 2015;Drenovsky et al, 2010;Steenwerth et al, 2003). Land-use effects on soil microbial communities are thought to be mediated mostly through alteration of soil properties.…”
Section: Introductionmentioning
confidence: 99%
“…Variables such as infrastructure inside protected areas (Pullin et al 2013), transport options to protected areas as Chile boast an extensive public transportation network (Spenceley et al 2015), biophysical attributes such as climate and elevation, and sociodemographic characteristics at the individual level such as age, gender and education (Booth et al 2010) could also drive visitation patterns. We were unable to identify clear (Castañeda et al 2015), and the wine industry is interested in environmentally-friendly practices, setting aside native forest for conservation, and ecotourism (Merelender et al 2014). The forestry industry, through engagement with the Forest Stewardship Council certification program, is also setting aside an important amount of native forest for conservation, especially in the Nahuelbuta coastal range (Pauchard et al 2007).…”
Section: Discussionmentioning
confidence: 99%